AKSIOLOGI PENDIDIKAN ISLAM DALAM PERSPEKTIF ISLAM DAN BARAT - Ahmad Dzulkifli; I'anatul Maula, Nur Fiki (CV. Kalimasada Group Profesional, 2025)
Abstract Axiology of education examines the values underlying the goals, processes, and outcomes of education. From an Islamic perspective, education is rooted in spiritual, ethical, and moral values derived from the Quran and Hadith, aiming to shape individuals who are devout, morally upright, and capable of fulfilling their roles as stewards (khalifah) on Earth. Conversely, the Western perspective emphasizes pragmatic and secular values, focusing on logic, rationality, and individual achievements in economic, technological, and social aspects. This study employs a qualitative approach based on library research to analyze the core values and differences in educational objectives between Islamic and Western perspectives. The findings reveal that Islamic education integrates worldly and spiritual dimensions, while Western education primarily focuses on secular life. This article contributes to developing a holistic and relevant paradigm of Islamic education that addresses contemporary challenges. Keywords: Axiology, Islamic, Western